The Analysis of Critical Factors for Science Parks with Emphasis on the Venture Capital Fund Provided by Science Parks - Čížek, Petr (Vysoká škola báňská-Technická univerzita Ostrava, 2015)
The paper deals with the perception of the science park business tenants to the different critical factors of the science park with emphasis on the idea of venture fund provided by science park. The quality factors of the science park are clustered into three groups (locality factors, quality factors and financial factors). The paper compares perception of these factors and it shows the role (and importance) of the venture fund to the tenants. In the conclusion the contribution gives recommendations for the science parks' managers and other possible investors which are willing to invest into high-risk but high-revenue industry.
Analýza kritických faktorů v podnikatelských inkubátorech s akcentem na venture kapitálový fond
Keywords: venture capital; science park; startup; investment; rizikový kapitál; vědecký park; startup; investice